Indicators Of Sewing and Knitting Enterprises in Our Republic - Sotvoldiyeva Nasibakhan (Genius Publishing Group, 2024)
Ush in the article in our country production being released sewing and knitting of our products volume and for export laying down Europe requirements analysis given
Keywords: Export; Organic; International market; BCSI